Description of Physical Activity and Nutritional Status of Students in primary school Country Bendungan Kec. Pabelan Kab. Semarang - Cahyo Wibowo; Venti Agustina; Tri Ari Kusnanto (Journal Physical Education, Health and Recreation, 2021)
Physical activity is a movement that is obtained from the work of the skeletal muscles which require energy. Physical activity requires energy, depending on the intensity and work of the muscles. Nutritional status is a health condition that is built by nutrient intakes. The method in this research is descriptive quantitative research. The research respondents consisted of 52 students of class IV-VI. Physical activity data techniques used the PAQ-C (Physical Activity Questionnaire For Children) questionnaire and nutritional status used anthropometric measurements with body weight and height measurements, calculated using the BMI (Body Mass Index) formula. The results showed that most of the students at SDN Bendungan Kec. Pabelan Kab. Semarang. The results of the most physical activity were in the moderate category as many as 25 students with a proportion (48%) of 52 students, and while for the most nutritional status in the normal category, there were 29 students with a proportion (55.7%).